Irregular meal pattern and later sleep midpoint are associated with increased BMI z-score and waist–height ratio during early adolescence - Lommi, Sohvi; Engberg, Elina; Lehtimäki, Aku-Ville; Lehto, Reetta; Viljakainen, Heli (Frontiers in Pediatrics, 2024)
Background Rapid gains in adiposity might have more adverse health implications in later life compared with having stable adiposity throughout childhood and adolescence. A gap of knowledge concerns concomitant health behaviors contributing to adiposity gain among adolescents.Objectives We investigated associations of health behaviors relating to dietary habits, sleep, physical activity and screen time with an increase of body mass index z-score (BMIz) and waist-height ratio (WHtR) during adolescence.We included 4785 adolescents (girls 53%) aged 11.1 (SD 0.8) years at baseline and followed them for three years. We clustered them into decreased, stable, and increased BMIz and WHtR categories using K-means clustering method. Using Cox regression, we computed hazard ratios (HR) with 95% confidence intervals (CI) for the associations of self-reported health behaviors (dietary habits, physical activity, sleep midpoint, and sedentary digital media use) with belonging to an increased BMIz or WHtR group. In a subsample (n = 3840), we ran a sensitivity analysis considering puberty status as an additional covariate.Later sleep midpoint (having later midpoint of sleep between bedtime and waking time) and irregular meal pattern (not eating lunch and dinner every school day) predicted increased BMIz (HR 1.26 [95%